Analysis of wearing-out causes for revolving-blade mixers and their reliability improvement - Jurevičius, Jurgis; Sivilevičius, Henrikas; Spruogis, Bronislovas (Transport, 2003)
In road coverings and structures of transport infrastructure, composite mixes of various compositions are used made with either organic or mineral binding agents. Most often they are made in a discreet revolving-blade forced mixer, and the final product quality is subject to the mixer construction and parameters. The present paper analyzes wear causes of a revolving-blade mixer with the most important of them-sticking of grains between the blade end and the bottom. Forces are defined effecting various-sized grains found between the blade end and the mixer bottom. Mixer quality assessment methodology is presented, based on analysis principles of homogeneity dynamics for mix being made by it. It is demonstrated that construction homogeneity estimates are different for mixers with various wearing-out levels. Wearing-out of mixer elements may be reduced and mixing quality for mix may be improved by choosing the optimum distance between the blade end and the bottom fretting and changing blade metal and dimensions. Elastic centrifugal coupling is recommended to decrease transmission strokes. First Published Online: 19 Dec 2011